An efficient proxy adaptive gateway discovery algorithm based on quality of service parameters. (2016) - Srivastava, Prakash; Kumar, Rakesh
Integration of MANET with internet requires gateways for increasing its usability and accessibility to fixed IP networks. However, such integrations prove complex owing to differences in mobility, routing and addressing between mobile ad hoc networks and fixed IP networks. Existing gateway discovery schemes suffer from low network throughput and performance trade-off. In our proposed gateway discovery scheme, apart from considering timestamp factor, hop count and interface queue length for selection of an optimal gateway, stability of link along the route is also taken into account. Stability of link ensures that message exchange after gateway discovery procedure will not be lost during transit. The proposed approach performance is evaluated through simulation and also analytically validated. Results show our approach has found to be outperforming other ones.